Tujuan Pendidikan dalam Hadis - Hazmi, Deni; Azhar, Ahmad; Fadly, Mhd Farizal; Lubis, Zulfahmi; Basri, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Education is the most important element for humans to increase their level of faith in Allah SWT. Humans, if they understand more about the basics of Islamic education, they will know and understand more. the creation of a faithful servant. Educational goals will determine the direction in which students will be taken. The aim of Islamic education in general is to foster human awareness as creatures of Allah SWT. so that they grow and develop into human beings who have noble character and worship Him. With a solid and strong foundation, of course in the end you will be able to realize maximum educational goals, which is to create a quality human figure in accordance with Islamic teachings which are guided by the Al-Qur'an and the Hadith of the Prophet SAW. The research used in this study is a type of research examining books. Reviewing a book is the activity of examining and studying a work, idea or problem in depth to reach conclusions. Likewise, in the hadiths, you can find many prophetic hadiths related to education (the goals of education). The position of hadith in Islamic religious education is the basis and foundation for the concept, framework and design of Islamic religious education considering that hadith provide more concrete reasons regarding the application of various activities that must be developed in Muslim life. Thus, the author will outline the discussion regarding